2012
DOI: 10.1016/j.neuro.2012.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Association between polychlorinated biphenyls and Parkinson's disease neuropathology

Abstract: Polychlorinated biphenyls (PCBs) are synthetic chemicals primarily used as coolants and insulators in electrical equipment. Although banned for several decades, PCBs continue to exist in the environment because of their long half-life, continued presence in items produced before the ban, and poor disposal practices. Epidemiological and experimental studies have identified exposure to PCBs as a potential risk factor for Parkinson’s disease, perhaps more so in females. The objective of this work was to examine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(39 citation statements)
references
References 28 publications
2
37
0
Order By: Relevance
“…We observed that genetic VMAT2 deficiency in vivo drives catecholamine depletion in the central nervous system and heart and increases relative cytosolic catecholamine catabolism by MAO. These findings in transgenic mice bear particular relevance to the pathology of PD where vesicular function may be compromised as a consequence of exogenous insult (Corrigan et al, 1998; Hatcher-Martin et al, 2012), genetic polymorphism (Brighina et al, 2013; Glatt et al, 2006; Uhl et al, 2000), or a cytosolic milieu that favors an oxidative state, especially with mitochondrial dysfunction (Schapira, 2011) and aging (Cruz-Muros et al, 2008). Indeed, post-mortem analysis of putamen tissue has revealed that PD patients exhibit neurochemical indices of reduced vesicular uptake of DA and buildup of DOPAL, a toxic MAO metabolite of DA (Goldstein et al, 2013).…”
Section: Discussionmentioning
confidence: 92%
“…We observed that genetic VMAT2 deficiency in vivo drives catecholamine depletion in the central nervous system and heart and increases relative cytosolic catecholamine catabolism by MAO. These findings in transgenic mice bear particular relevance to the pathology of PD where vesicular function may be compromised as a consequence of exogenous insult (Corrigan et al, 1998; Hatcher-Martin et al, 2012), genetic polymorphism (Brighina et al, 2013; Glatt et al, 2006; Uhl et al, 2000), or a cytosolic milieu that favors an oxidative state, especially with mitochondrial dysfunction (Schapira, 2011) and aging (Cruz-Muros et al, 2008). Indeed, post-mortem analysis of putamen tissue has revealed that PD patients exhibit neurochemical indices of reduced vesicular uptake of DA and buildup of DOPAL, a toxic MAO metabolite of DA (Goldstein et al, 2013).…”
Section: Discussionmentioning
confidence: 92%
“…Despite its removal from gasoline and most paint products, lead remains a ubiquitous environmental pollutant. Biologically plausible relationships have been suggested with other pervasive environmental exposures, such as polychlorinated biphenyls and urban air pollution, but the findings are inconsistent.…”
Section: The Past 10 Yearsmentioning
confidence: 99%
“…In a retrospective mortality study examining PCB exposure amongst workers in capacitor plants, sex-specific analyses found higher deaths from PD amongst exposed women [140]. In a case-control study examining post-mortem brain tissue from PD, AD, and control patients, PCB levels were higher in PD groups, and when stratified by age, were higher amongst women [141]. …”
Section: Epidemiologic and Experimental Evidence Of Brain Health Dmentioning
confidence: 99%